SUBARACHNOID HAEMORRHAGE ASSOCIATED WITH CEREBRAL SINUS THROMBOSIS – A RARE CASE - Veljanovski, Dimitar; Kostova, Masha; Prgova, Biljana; Dejanova, Sandra; Deleva-Stoshevska, Tatjana; Ristikj-Stomnaroska, Daniela (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Cerebral venous thrombosis is a condition that requires greater clinical and radiological experience due to the significantly wider range of clinical signs and significant radiological variability. When the patient presents with SAH (subarachnoid haemorrhage), the challenge can be great. We present a case of cerebral venous thrombosis that radiologically presented with SAH without initial involvement of the parenchyma, which is why early diagnosis was important. We present a 36-year-old patient, with clinical manifestation of acute headache, elements for SAH on CT (computerised tomography) without initial involvement - haemorrhage of the brain parenchyma. CT angiography and venography using MRI (magnetic resonance imaging) demonstrated extensive thrombosis of the jugular vein, sigmoid and transverse sinus, with no other cause for SAH. Complete recanalization of the venous sinuses and significant improvement of the clinical diagnosis were reached after adequate anticoagulation therapy. The findings indicated that venous sinus thrombosis may initially manifest as unilateral SAH without the involvement of the brain parenchyma. Keywords: cerebral venous thrombosis, subarachnoid haemorrhage, CT and MRI venography, acute headache